Online hybrid test by internet linkage of distributed test-analysis domains. - Pan, Peng (Earthquake engineering & structural dynamics.)
Online hybrid tests (called the online tests), particularly when combined with substructuring techniques, are able to conduct large scale tests. An extension of this technique is to combine multiple loading tests conducted in remote locations and to integrate the tests with large numerical analysis codes. In this study, a new Internet online test system is developed in which a physical test is conducted in one place, the associated numerical analysis is performed in a remote location, and the two locations communicate over the Internet. To implement the system, a technique that links test and analysis domains located at different places is proposed, and an Internet data exchange interface is devised to allow data communication across Internet. A practical method that utilizes standard protocols implemented by operating systems for sharing files and folders is adopted to ensure stable and robust communication between remotely located servers that commonly protect themselves by strict firewalls. To combine the online test with a finite element program formulated in an incremental form and adopting an implicit integration scheme, a tangent stiffness prediction procedure is proposed. In this procedure, a tangent stiffness is estimated based on a few previous steps of experimental data. Using the system devised, tests on a base-isolated structure were carried out. Here, the base-isolation layer was taken as the tested part and tested in Kyoto University, Japan, and the superstructure was modelled by means of a finite element program and analysed in a computer located in Osaka University. A series of physical Internet online tests were carried out, with the integration time interval and the method of tangent stiffness prediction as the major parameters. The tests demonstrated that the Internet communication was very stable and robust, without malfunctions. The proposed method of stiffness prediction was effective even when the experimental hysteresis curves exhibited complex behaviour, thereby ensuring accurate simulation for the earthquake response of the entire structure.